"Food addiction" is associated with night eating severity. (1st March 2016) - Nolan, Laurence J.; Geliebter, Allan
Abstract: Night eating syndrome (NES) and "food addiction" (FA) are associated with elevated body mass index (BMI) and disturbed eating behavior. The present study was conducted to examine whether NES is associated with FA, and whether BMI, depression and sleep quality contribute to any relationship between NES and FA. Two groups were studied: a sample of 254 university students and a sample of 244 older adults. All completed the Yale Food Addiction Scale (YFAS), the Night Eating Questionnaire (NEQ), the Zung Self-report Depression Scale, and the Pittsburgh Sleep Quality Index, and BMI was computed from height and weight. In both samples, higher global NEQ scores were significantly correlated with more FA symptoms, elevated depression, and poorer sleep quality, and these correlations were significantly higher in the older adult sample than in the younger student sample. Higher BMI was significantly correlated with NEQ score only in the older adult sample. The hypothesis that the prediction of NEQ by YFAS was moderated by BMI and group membership (moderated moderation) was tested; while the prediction of NEQ by YFAS was not moderated by BMI, elevated YFAS predicted higher NEQ in the adult sample than it did in the student sample. In addition, multiple regression revealed that "continued use of food despite adverse effects" was the sole FA symptom predictive of NES symptoms in students while in older adults food tolerance was the only predictor of NES. Thus, NES appears to be associated with FA, more strongly in an older community sample; higher food tolerance in NES may contribute to a desire to eat late in the evening and/or when awakening at night. Highlights: Relationship between night eating syndrome (NES) and food addiction (FA) was studied. NES was associated with FA when accounting for BMI, sleep quality, and depression. Food tolerance predicted NES in older adults; food use despite harm did in students. FA predicted NES more strongly in older participants; the relationship was not moderated by BMI. In adults, food consumption at night in NES may be subject to food tolerance.